-x2 + 2x + 48 = (x +6)(8 - x)
x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7
x2 + 2x - 15 = (x - 3)(x + 5)
x2 + 2x - 15 = (x + 5)(x - 3)
x3 - x2 + 2x = x*(x2 - x + 2) which cannot be factored further.
Factor it out: (x+2) squared
It is: 4x -34x^2 -21 simplified
-x2 + 2x + 48 = (x +6)(8 - x)
x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7
X2+Y3+15 All you can do is simplify it.
-x2 + 2x + 48 = (-x - 6)(x - 8)
x2+2x-63 = (x-7)(x+9) when factored
x2 + 2x - 15 = (x - 3)(x + 5)
x2 + 2x - 15 = (x + 5)(x - 3)
x3 - x2 + 2x = x*(x2 - x + 2) which cannot be factored further.
2x2 + x2 = 3x2
2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0